TRPC3 cation channel plays an important role in proliferation and differentiation of skeletal muscle myoblasts - Woo, Jin Seok (Korean Society for Biochemistry and Molecular Biology, 2010)
During membrane depolarization associated with skeletal excitation-contraction (EC) coupling, dihydropyridine receptor [DHPR, a L-type Ca(2+) channel in the transverse (t)-tubule membrane] undergoes conformational changes that are transmitted to ryanodine receptor 1 [RyR1, an internal Ca(2+)-release channel in the sarcoplasmic reticulum (SR) membrane] causing Ca(2+) release from the SR. Canonical-type transient receptor potential cation channel 3 (TRPC3), an extracellular Ca(2+)-entry channel in the t-tubule and plasma membrane, is required for full-gain of skeletal EC coupling. To examine additional role(s) for TRPC3 in skeletal muscle other than mediation of EC coupling, in the present study, we created a stable myoblast line with reduced TRPC3 expression and without α1(S)DHPR (MDG/TRPC3 KD myoblast) by knock-down of TRPC3 in α1(S)DHPR-null muscular dysgenic (MDG) myoblasts using retrovirus-delivered small interference RNAs in order to eliminate any DHPR-associated EC coupling-related events. Unlike wild-type or α1(S)DHPR-null MDG myoblasts, MDG/TRPC3 KD myoblasts exhibited dramatic changes in cellular morphology (e.g., unusual expansion of both cell volume and the plasma membrane, and multi-nuclei) and failed to differentiate into myotubes possibly due to increased Ca(2+) content in the SR. These results suggest that TRPC3 plays an important role in the maintenance of skeletal muscle myoblasts and myotubes.